2016
DOI: 10.1021/acs.jpcc.6b01675
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Triphenylamine–Thiophene–Azomethine Derivatives: Toward Understanding Their Electrochromic Behavior

Abstract: A series of thiophenoazomethines connected to a central triphenylamine were prepared. The effect of the type of aminothiophene used to prepare the conjugated azomethines and the number of azomethine bonds, ranging from one to three, flanking the triphenylamine on the spectral, electrochemical, and spectroelectrochemical properties were investigated. Both the absorption and fluorescence of the azomethines (6–8) derived from 2,5-diaminothiophene (1) were found to be contingent on the number of the azomethines. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…For TPA-OMeTPA we observed that the HOMO is more localized on the terminal triphenylamines, which we ascribe to the disruption of the conjugation of the central triphenylamine. [46,47] The disturbance of the conjugation in the triphenylamine-based azomethines was experimentally observed by Skene and co-workers in a previous study. [47] HOMO energy levels obtained from computational chemistry for single molecules in vacuum generally strongly differ from the experimentally results.…”
Section: Computational Studymentioning
confidence: 83%
See 1 more Smart Citation
“…For TPA-OMeTPA we observed that the HOMO is more localized on the terminal triphenylamines, which we ascribe to the disruption of the conjugation of the central triphenylamine. [46,47] The disturbance of the conjugation in the triphenylamine-based azomethines was experimentally observed by Skene and co-workers in a previous study. [47] HOMO energy levels obtained from computational chemistry for single molecules in vacuum generally strongly differ from the experimentally results.…”
Section: Computational Studymentioning
confidence: 83%
“…[46,47] The disturbance of the conjugation in the triphenylamine-based azomethines was experimentally observed by Skene and co-workers in a previous study. [47] HOMO energy levels obtained from computational chemistry for single molecules in vacuum generally strongly differ from the experimentally results. Chi et al showed that it is possible to get a good estimate of the experimental HOMO energy levels from the HOMO energy levels obtained from DFT calculations (B3LYP/6-31G(d,p) in dichloromethane) [45] using the following formula:…”
Section: Computational Studymentioning
confidence: 92%
“… 9 , 10 These types of materials were extensively studied due to their interesting thermal, 11 electrical, 12 and optical 13 15 properties and also due to the possible activity in some optoelectronic systems, such as bulk heterojunction photovoltaic cells, 16 19 perovskite solar cells, 20 22 organic light-emitting devices, 23 , 24 or electrochemical systems. 25 , 26 …”
Section: Introductionmentioning
confidence: 99%
“…The electron density in the case of HOMO energy levels of both the compounds is located on the electron-donating triarylamine units, while the LUMO energy levels are spread over the electron-withdrawing azomethine linkage and the aryl spacer unit between phenothiazine and azomethine(s). 41 , 42 Simulations of the vertical excitations of AZO-III and AZO-IV indicate that the first transition refers to the HOMO–LUMO transitions ( Tables S2 and S3 ) through intramolecular charge transfer.…”
Section: Resultsmentioning
confidence: 99%